2019
DOI: 10.1080/03008207.2019.1688314
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling and the transcription factor Foxn1 contribute to cutaneous wound repair in mice

Abstract: Aim: The transcription factor Foxn1 is a regulator of scar-ended cutaneous wound healing in mice. However, the link between Foxn1 and Wnt signaling has not been explored in the context of cutaneous repair. Here, we investigate the effects of β-catenin-dependent and-independent Wnt signaling represented by Wnt10a and Wnt11, respectively, in healing of full-thickness cutaneous wounds in C57BL/6 mice. Material and Methods: Quantitative polymerase chain reaction, western blot, and immunostaining were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
14
0
3
Order By: Relevance
“…On the contrary, regular cutaneous wound repair involves excessive deposition of extracellular matrix (ECM), mainly collagen type I [ 9 , 10 ], an increase in Tgfβ1 level [ 8 ], and differentiation of dermal fibroblasts (DFs) into myofibroblasts [ 11 ]. Additionally, recent studies on mouse models of wound healing demonstrate that the Wnt pathway contributes to the cellular response to the injury and promotes the development of scar tissue [ 12 , 13 ]. We have previously shown that the expression levels of Wnt10a and Wnt11, the representatives of Wnt/β-catenin-dependent and Wnt/β-catenin-independent pathways, respectively, increase early during the remodeling phase and might contribute to ECM deposition during cutaneous healing in mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, regular cutaneous wound repair involves excessive deposition of extracellular matrix (ECM), mainly collagen type I [ 9 , 10 ], an increase in Tgfβ1 level [ 8 ], and differentiation of dermal fibroblasts (DFs) into myofibroblasts [ 11 ]. Additionally, recent studies on mouse models of wound healing demonstrate that the Wnt pathway contributes to the cellular response to the injury and promotes the development of scar tissue [ 12 , 13 ]. We have previously shown that the expression levels of Wnt10a and Wnt11, the representatives of Wnt/β-catenin-dependent and Wnt/β-catenin-independent pathways, respectively, increase early during the remodeling phase and might contribute to ECM deposition during cutaneous healing in mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent studies on mouse models of wound healing demonstrate that the Wnt pathway contributes to the cellular response to the injury and promotes the development of scar tissue [ 12 , 13 ]. We have previously shown that the expression levels of Wnt10a and Wnt11, the representatives of Wnt/β-catenin-dependent and Wnt/β-catenin-independent pathways, respectively, increase early during the remodeling phase and might contribute to ECM deposition during cutaneous healing in mice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescencyjna detekcja E-kadheryny w pourazowej skórze myszy transgenicznych Foxn1: eGFP. br-brzeg rany, nk-naskórek, sw-skóra właściwa, strzałki wskazują mieszki włosowe, linia przerywana oddziela naskórek od skóry właściwej [63]. Komórki naskórka myszy Foxn1-eGFP wykazywały kolokalizację z WNT11, który jest elementem szlaku zaangażowanego w regulację ekspresji FOXN1 w grasicy.…”
Section: Foxn1 Jako Regulator Bliznowego Vs Bezbliznowego Gojenia Urazów Skóryunclassified
“…Komórki naskórka myszy Foxn1-eGFP wykazywały kolokalizację z WNT11, który jest elementem szlaku zaangażowanego w regulację ekspresji FOXN1 w grasicy. Wskazuje to na udział szlaku WNT w regulacji FOXN1 również w skórze [63].…”
Section: Foxn1 Jako Regulator Bliznowego Vs Bezbliznowego Gojenia Urazów Skóryunclassified
See 1 more Smart Citation